Analysis of Service Quality to Increase Customer Satisfaction at Retail Industry - Samdrup Rigyal (Yayasan Gema Bina Nusantara, 2023)
The aim of this research is to measure the level of service that the retail store has provided to its consumers. In this study, the sample used was students; there were approximately 34 respondents. This research uses primary data because primary data was obtained through distributing questionnaires to students. From the results of the study, it was obtained that each component or question was carried out in research studies, where Q1, Q5, and Q7 need to be considered because they have the smallest gap value with the number -0.3, which with these results can provide retail stores with more components in the quadrant. Indicators included in quadrant 1 are indicators that consumers think are important, but the performance shown by the company is poor. Indicators that fall into quadrant 2 are indicators that consumers think are important, and the performance of the company itself is also good. Between importance and performance, we have found a middle point. Indicators included in quadrant 3 are of low importance. This is because, according to consumers, after experiencing it directly, it is not important, and the company's performance is also poor. Indicators included in quadrant 4 are low-importance, high-performance indicators. This is because, according to consumers, this indicator is not important, but the company shows good performance.